Teachers’ Implementation of Inclusive Teaching Practices as a Potential Predictor for Students’ Perception of Academic, Social and Emotional Inclusion - Alnahdi, Ghaleb H.; Lindner, Katharina-Theresa; Schwab, Susanne (Frontiers in Psychology, 2022)
The aim of the current study was to illustrate the impact of teachers’ implementation of differentiation and individualization (perceived by students) on students’ perception of their inclusion regarding their social inclusion, emotional wellbeing and academic self-concept.. The study sample comprised 824 third-to eighth-grade students (255 males [31%] and 569 females [69%]). Around 10% of the sample (82) had special educational needs (SEN). Students’ perceived inclusion levels and academic self-concept were examined with the Arabic version of the Perceptions of Inclusion Questionnaire (PIQ-S-AR). Students’ ratings of inclusive practices in their classroom were examined using the Arabic version of the inclusive teaching practices scale (ITPS). SEN students expressed lower perceived social inclusion, emotional inclusion, and academic self-concept in comparison to non-SEN students. Moreover, high levels of inclusive teaching practices strongly predicted students’ perceived emotional inclusion, social inclusion, and academic self-concept. The results of the study supported the importance of school-level inclusive teaching practices and their relation to students’ school experiences. It also highlighted the need for schools and teachers to work towards improved school-level inclusion experiences for SEN students.